Dynamic teaching of Russian: games and gamification of learning - Nuss, Svetlana V.; Kogan, Vita V. (Routledge, 2023)
Teaching language with games : practice, research, and cohesion of pedagogy / Svetlana V. Nuss -- Gamification and game-based learning : an overview and application to language teaching / Vita V. Kogan -- Using mingling games with beginner learners / Daria Kotelnikova and Elena Bogomolova -- Trivia games for student-centered learning in the Russian language classroom / Maria Khotimsky -- The use of authentic games in teaching L2 Russian grammar / Anna Leontyeva and Ekaterina Schnittke -- Learning motion verbs through a board game : insights from a cognitive linguistics perspective / Maria Bondarenko -- Game-based learning in L2 Russian classrooms : interaction, multimodality, and practical suggestions / Olesia Pavlenko and Dmitrii Pastushenkov -- Ludic acts of language acquisition : role, dialogue, and stage for L2 Russian oral proficiency / Susanna Weygandt -- "I like brown, eyes, potatoes:" gamified poetry for beginners / Polina Peremitina -- Playing at conversation : chatbots in Russian language teaching / Daria Dornicheva and Sandra Birzer -- Teaching language with games : are the games worth the candle? Reflections on practice and future directions / Vita V. Kogan and Svetlana V. Nuss.